Dissolved gas and solute concentrations in surface and soil waters of an Arctic water track, Upper Kuparuk River Basin, Alaska, 2013 ... - Harms, Tamara (Arctic Data Center, 2020)
This research evaluates how climate-induced changes in water and nutrient cycles on land are propagated to stream networks. Increased export of water and the nutrients nitrogen and phosphorus from river networks to the Arctic Ocean reflects shifts in patterns of water and nutrient movement in the arctic. Changing climate may contribute to such shifts by causing release of nutrients from thawing permafrost, altering precipitation patterns, increasing rates of biogeochemical reactions, or expanding storage capacity in thawed soils. These changes may have far-reaching effects because flowing water connects land to downstream aquatic ecosystems, but the flowpaths connecting terrestrial ecosystems to stream networks remain poorly understood. This research focuses on transport and reaction of water and solutes within water tracks, which are linear regions of surface and subsurface flow that connect hill slopes to streams and account for up to 35% of watershed area in arctic tundra. Specific objectives are to: 1) ...